2010
DOI: 10.1021/ja1089777
|View full text |Cite
|
Sign up to set email alerts
|

Two-Coordinate First Row Transition Metal Complexes with Short Unsupported Metal−Metal Bonds

Abstract: A series of first row transition metal complexes with unsupported M-Fe bonds, (3,5-(i)Pr2-Ar*)MFe(η(5)-C5H5)(CO)2 (M = Fe (1), Mn (2), Cr (3), 3,5-(i)Pr2-Ar* = -C6H-2,6-(C6H2-2,4,6-(i)Pr3)2-3,5-(i)Pr2), was synthesized by salt metathesis. They were characterized by (1)H NMR, UV-vis spectroscopy, X-ray crystallography, and SQUID magnetic measurements. Two distinct Fe atoms in 1 were confirmed by Mössbauer spectroscopy. All three compounds feature short metal-metal bond distances (Fe-Fe, 2.3931(8) Å (1); Mn-Fe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 50 publications
3
39
0
2
Order By: Relevance
“…However, two-coordinate transition-metal complexes, [R*MFe(η 5 -C 5 H 5 )(CO) 2 ] (M = Fe, Mn, Cr; R* = -C 6 H-2,6-Ar 2 -3,5-i Pr 2 where Ar = -C 6 H 2 -2,5,6-i Pr 3 ), were synthesized and isolated. 61 As might be apparent from Figure 29, the bulky R* group surrounds the two-coordinate M atom and blocks the formation of any third bond to M. X-ray crystal analysis showed that the metalmetal bond distances are 2.393 ¡ for FeFe, 2.451 ¡ for MnFe, and 2.489 ¡ for CrFe. These metalmetal bond distances are much shorter than those of the known complexes with unsupported FeFe (2.6873.138 ¡), MnFe (2.6012.843 ¡), and CrFe Figure 29b.…”
Section: ¹1mentioning
confidence: 97%
See 2 more Smart Citations
“…However, two-coordinate transition-metal complexes, [R*MFe(η 5 -C 5 H 5 )(CO) 2 ] (M = Fe, Mn, Cr; R* = -C 6 H-2,6-Ar 2 -3,5-i Pr 2 where Ar = -C 6 H 2 -2,5,6-i Pr 3 ), were synthesized and isolated. 61 As might be apparent from Figure 29, the bulky R* group surrounds the two-coordinate M atom and blocks the formation of any third bond to M. X-ray crystal analysis showed that the metalmetal bond distances are 2.393 ¡ for FeFe, 2.451 ¡ for MnFe, and 2.489 ¡ for CrFe. These metalmetal bond distances are much shorter than those of the known complexes with unsupported FeFe (2.6873.138 ¡), MnFe (2.6012.843 ¡), and CrFe Figure 29b.…”
Section: ¹1mentioning
confidence: 97%
“…These metalmetal bond distances are much shorter than those of the known complexes with unsupported FeFe (2.6873.138 ¡), MnFe (2.6012.843 ¡), and CrFe Figure 29b. 61 It was calculated that the FeFe bond distance of 2.403 ¡ is shortened to 2.362 ¡ upon the replacement of the R* group by the much smaller Ph group, which suggests that the metal metal bond distance of [R*FeFe(η 5 -C 5 H 5 )(CO) 2 ] is elongated somewhat by the bulky R* group. It was considered that the nearly linear structure at the two-coordinate Fe atom was supported by the bulky R* group.…”
Section: ¹1mentioning
confidence: 99%
See 1 more Smart Citation
“…1 In terms of structure and bonding, the investigation of metal-metal bonds within heterobimetallic complexes is particularly attractive due to the differing electronegativities of the metal centres resulting in ionic contributions to the bonding. 2 Despite the potential cooperative reactivity between two metal centres with very different electronic configurations, heteronuclear compounds with highly polar metal-metal bonds have historically proven challenging to study as the differing redox properties of these metals have often prevented their synthesis and isolation. 3 It is the investigation of such heterobimetallic compounds which do not exhibit bridging ligands which is a particular area of interest as the degree of covalent contributions to the bonding in heteronuclear metal-metal bonds cannot be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Zweifach koordinierte Komplexe wurden vor allem mit 3d-Übergangsmetal-len isoliert, da das Metallzentrum wegen seiner geringen Größe leichter fähig ist, eine Koordination zusätzlicher Donoren zu blockieren. [2] Bemerkenswert ist ein neuer Beitrag von Power et al, [4] in dem neuartige, zweifach koordinierte Komplexe vorgestellt werden, in denen ein Teil der sterischen Abschirmung nicht von organischen Hilfsliganden wie denen in Schema 1, sondern von einem zweiten Metallfragment herrührt, das eine Metall-Metall-Bindung eingeht. Komplexe dieser Art, die Metall-Metall-Bindungen zwischen Metallenzentren unterschiedlichen Charakters enthalten, wurden als "xenophil" bezeichnet.…”
unclassified